Pengaruh Buku Cerita Terhadap Peningkatan Sikap Peduli Kebersihan Lingkungan Sekolah pada Anak Kelas V Sekolah Dasar di Kecamatan Gamping Kabupaten Sleman Propinsi Daerah Istimewa Yogyakarta - Yustiana Olfah; Ni Ketut Mendri; Bondan Palestin (LPPM STIKES Guna Bangsa, 2017)
Background: Elementary school education is the basic level education where students were forged with many kind of study subject where each subject has to be mastered by the students. On the other hand students were also educated with attitude and behavior values that will be the basis for further developments in the future. One of the important attitude and behavior that needs to be educated early is environmental hygiene concern. Story book is a proper medium for attitude and behavior educaton for children, since they can accommodate children reading capacity and interest. Story books are usually written with short sentence, also simpler vocabulary and grammar compared to adult reading which makes them very effective in affecting the soul of the children. Objectives: To reveal the influence of story book with hygiene environmental schools hygiene concern theme towards attitudes and behavior of hygiene environmental schools hygiene concern on students of elementary schools in the District Gamping, Sleman Special Region of Yogyakarta. Method : Quasi-experimental